« Des gens dans la carte ». Une géographie des individus pour enseigner les questions migratoires - Pascal Clerc (EchoGéo)
The geographical teaching of migratory issues in France is based, on one hand, on statistics and maps that give an overview, and on the other hand, less frequently, on life stories. Both practices are necessary to understand the migrations. The daily lives of migrants, their emotions and sensations are as important as the general data. This text proposes to introduce "people in the map" to teach the complexity of migration. based on life stories and fictional forms of discourses.